Effect of 8-Hydroxyguanine DNA Glycosylase 1 on the Function of Immune Cells - Weiran Zhang; Ranwei Zhong; Xiangping Qu; Yang Xiang; Ming Ji (MDPI AG, 2023)
Excess reactive oxygen species (ROS) can cause an imbalance between oxidation and anti-oxidation, leading to the occurrence of oxidative stress in the body. The most common product of ROS-induced base damage is 8-hydroxyguanine (8-oxoG). Failure to promptly remove 8-oxoG often causes mutations during DNA replication. 8-oxoG is cleared from cells by the 8-oxoG DNA glycosylase 1 (OGG1)-mediated oxidative damage base excision repair pathway so as to prevent cells from suffering dysfunction due to oxidative stress. Physiological immune homeostasis and, in particular, immune cell function are vulnerable to oxidative stress. Evidence suggests that inflammation, aging, cancer, and other diseases are related to an imbalance in immune homeostasis caused by oxidative stress. However, the role of the OGG1-mediated oxidative damage repair pathway in the activation and maintenance of immune cell function is unknown. This review summarizes the current understanding of the effect of OGG1 on immune cell function.